2019
DOI: 10.1152/ajpheart.00697.2018
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II-induced hypertension and cardiac hypertrophy are differentially mediated by TLR3- and TLR4-dependent pathways

Abstract: Toll-like receptors (TLR) are key components of the innate immune system that elicit inflammatory responses through the adaptor proteins myeloid differentiation protein 88 (MyD88) and Toll-interleukin receptor domain-containing adaptor protein-inducing interferon-β (TRIF). Previously, we demonstrated that TRIF mediates the signaling of angiotensin II (ANG II)- induced hypertension and cardiac hypertrophy. Since TRIF is activated selectively by TLR3 and TLR4, our goals in this study were to determine the roles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 65 publications
1
34
1
Order By: Relevance
“…Recently studies have shown that TLR4 is an important receptor for the signaling transduction in the innate immune system, which affects various cardiovascular diseases such as heart failure and hypertension (Kandadi et al, 2012; Wang S.Y. et al, 2018; Dai et al, 2019; Singh et al, 2019). TLR4 has been recognized as an important regulator for NF-κB (Li et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recently studies have shown that TLR4 is an important receptor for the signaling transduction in the innate immune system, which affects various cardiovascular diseases such as heart failure and hypertension (Kandadi et al, 2012; Wang S.Y. et al, 2018; Dai et al, 2019; Singh et al, 2019). TLR4 has been recognized as an important regulator for NF-κB (Li et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the TRIF-dependent pathway is shown to be a determinant in hypertension and cardiac hypertrophy, whereas the MyD88-dependent pathway is not responsible (97). Indeed, in settings of Ang II infusions at high rates (3,000 ng/kg/min), cardiac hypertrophy was found to have been reduced in TRIF deficient mice but aggravated in MyD88 knockout mice compared to wild type mice by measuring the ratio of heart weight to body weight, with a similar trend also observed in systolic blood pressure (97,98). Furthermore, the inflammatory response not only did not decrease but increased in MyD88 deficient mice, accompanied by the increase in cardiac expression of TLR4 and TRIF, indicating that MyD88dependent signaling functions as a negative regulator of proinflammatory pathological response mediated by TRIF in the context of high dose Ang II-induced cardiac hypertrophy (97), and infusion doses of Ang II may cause MyD88-dependent signaling functions in cardiac hypertrophy differing from the usual response.…”
Section: Tlr4/trif Pathway In Cardiac Hypertrophymentioning
confidence: 85%
“…Furthermore, the inflammatory response not only did not decrease but increased in MyD88 deficient mice, accompanied by the increase in cardiac expression of TLR4 and TRIF, indicating that MyD88dependent signaling functions as a negative regulator of proinflammatory pathological response mediated by TRIF in the context of high dose Ang II-induced cardiac hypertrophy (97), and infusion doses of Ang II may cause MyD88-dependent signaling functions in cardiac hypertrophy differing from the usual response. On this basis, further studies demonstrated that activation of TRIF signaling releases type I IFNs that are responsible for Ang II-induced hypertension and cardiac hypertrophy, whereas the TLR3-mediated TRIF signaling not only induces hypertension but also cardiac hypertrophy in response to Ang II infusion, but the TLR4/TRIF pathway is only required for cardiac hypertrophy (98). However, it is not clear whether there are similar phenomena in pressure overloador obesity-induced cardiac hypertrophy model.…”
Section: Tlr4/trif Pathway In Cardiac Hypertrophymentioning
confidence: 99%
“…The latter is a factor of the innate immune system involved in system inflammation; in recent years, its putative role in the pathogenesis of HTN has emerged. Animal studies have shown how angiotensin II acts through the activation of TLR4 pathways; however, the precise mechanism has yet to be elucidated [111,147]. This study shows that probiotics represent a possible therapeutic tool for the treatment of genetic HTN.…”
Section: Probioticsmentioning
confidence: 85%